Studi Ekosistem Terumbu Karang di Taman Nasional Kepulauan Seribu - linda noviana (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Taman Nasional Laut Kepulauan Seribu (TNLKpS) has a unique natural resource is the natural beauty of the sea and coral ecosystems are unique. But along with the rapid population growth of Jakarta as the capital city and the increasing number of tourists also affect the condition of coral reefs in TNLKpS. This study aimed to analyze and assess the ecological condition of coral reef ecosystems in the utilization zone travel TNLKpS by coral cover life and death, diversity as well as the factors causing the damage of the survey line intercept transect (LIT), literature review, interviews and analysis of the condition of coral reefs by Decree LH No. 4 of 2001 on Baku Criteria Damage Coral Karan. Condition of the reef by live coral cover otherwise damaged to moderate, based on the otherwise dead coral cover damaged high to moderate damage, then the number and type of reef fish more on the depth of 10 meters in comparison with 3 meters. Thecondition of coral reef ecosystems is common in 3 islands (Pulau Putri, Pulau Macan and Pulau Angin Angin Genteng) in TNKS is still quite good, but in some snorkeling spots it looks bad (3 stations) and medium (2 stations) when compared to spots diving (only 1 bad station).